Analisis Neutronik Teras RSG-Gas Berbahan Bakar Silisida - Tukiran S.; Tagor MS (Indonesian Journal of Physics, 2001)
RSG-GAS reactor has been starting to convert its fuels from original fuel, (oxide fuel U3O8Al) to uranium silicide fuel U3Si2Al with loading, density and enrichment similar to those of original fuel 250 g, 2.96 g/cm3, 19.75 %, respectively. For next future, the RSG-GAS is planning to use silicide fuel with loading, density and enrichment of 300 g, 3.55 g/cm3, 19.75 %, respectively because the higher density of silicide fuel used, the more advantages can be achieved for reactor operation. There for, it is necessary to analyze the feasibility of using silicide fuels with 300 g loading for RSG-GAS core. The kinetic and neutronic parameter were calculated by generating macroscopic cross section of 300 gr silicide fuel loading. The neutronic and kinetic parameter were calculated based on the macroscopic cross section. The macroscopic cross section calculation was done by WIMSD/4 code with 4 neutron energy group. Calculation result of macroscopic cross section was used to determine neutronic and kinetic parameter using Batan-2DIFF code. The result of analisis showed that the 300 gr sicilide fuel loading is feasible to be used in the RSG-GAS core without exceeded the safety margin.